MSK Ultrasound - An IJSPT Perspective - Phil Page; Robert C Manske; Michael Voight; Chris Wolfe (North American Sports Medicine Institute, 2023)
MSK ultrasound is a valuable imaging technique which has become increasingly popular in recent years. This efficient technique proves beneficial in a variety of ways. MSK ultrasound effectively streamlines the process by enabling practitioners to securely and accurately image and assess structures all in one simple step. By allowing healthcare providers to access critical information quickly and conveniently, MSK ultrasound can help identify conditions early when interventions are most effective. Moreover, it may be able to shorten diagnostic times and reduce costs through more cost-effective use of resources such as imaging and laboratory testing. Furthermore, MSK ultrasound can provide additional insights into musculoskeletal anatomy and help improve patient care and outcomes. In addition, utilizing this method reduces exposure to radiation and provides enhanced patient comfort with its quick scan duration. MSK ultrasound has a high potential to provide quick and accurate diagnosis of MSK disturbances when used correctly. As clinicians become more comfortable and familiar with this technology, we will continue to see its use expand for various MSK assessments. In this commentary we'll explore how ultrasound can be used in physical therapy, specifically for musculoskeletal assessment. We'll also look at some of the potential benefits and limitations of using ultrasound in PT practice.